Water Scarcity: A Global Issue - Jain, Sparsh (Journal of Advanced Research in Alternative Energy, Environment and Ecology, 2021)
This chapter explores about the problems that we are facing because of water scarcity. Water is very important in our life and its scarcity can lead us to many problems. Basically, water scarcity is the lack of sufficient available fresh water resources to meet water demand. It affects every continent and is the largest global risk. 0.014% of all water on Earth is both fresh and easily accessible. The unequal distribution results in some wet and some dry geographical locations. Today, humanity is facing water crisis and we are continuously wasting the water available with us. At the current consumption rate, the situation will only get worse. By 2025, two-thirds of the world’s population may face water shortage. There will be many affects of water scarcity such as lack of availability of drinking water, hunger, diseases, sanitation issues, etc. In Cape Town, forecasters have forecasted that the water available with them will last till 16 April. To use the available water for longer, South African Government has reduced the consumption of water from 87 liters to 50 liters a day. If we want to overcome this problem, then we must take certain steps. We must educate people not to waste the water, store water, etc so that this problem of water scarcity can be easily solved. How to cite this article: Jain S. Water Scarcity: A Global Issue. J Adv Res Alt Energ Env Eco 2018; 5(3): 12-14.